PRIORITY ISSUES FOR THE INTEGRATED MANAGEMENT OF THE WESTERN COASTAL ZONE OF THE GULF OF TONKIN - Thanh, Tran Duc (Vietnam Journal of Marine Science and Technology, 2009)
The priority issues for the integrated management of the Western coastal zone of the Gulf of Tonkin are identified based on the analysis of the data and doarments on the natural conditions and ecosystems, the state and tendency of the environment and resources; on the current status and the orientation of future socio - development; on the view point of the strategic, integrated, adaptative, and urgency nature of management issues; on the using methods of DPSIR model analysis (Drivers-Pressure-State-Impact-Response); on the spatial and temporal analysis; and on the development of matrix with weighting assessment. The analysis and selection of the priority have been performed for five management issues, and applied for the management models of 4 different spatial levels (the western coastal zone of Tonkin Gulf, the coastal region of the Bac bo, the coastal sub-region of Northeast Bac bo, and the coastal area of Haiphong) in three management periods: 2011 - 2015, 2016 - 2020, and 2021 - 2025. Beside of the coastal sub-region of Northeast Bac Bo, the estimation of priority issues were also made for the sub-regions of Thai Binh - Ninh Binh and Thanh Hoa – Quang Binh in the western coastal zone of the Gulf of Tonkin. The analysis shows that the management and rational use of natural resources are the first priority issue. The second priority is the management and prevention of pollution and environmental risks. These are priorities for all four spatial management levels, and for the entirely integrated management process. The natural and biodiversity conservation is placed at the forth for the western coastal zone of Tonkin Gulf and the coastal region of the Bac bo, but is the thirth priority for the coastal sub-region of Northeast Bac bo, and the coastal area of Haiphong. The management and prevention of pollution and natural disasters are considered as the thirth priority for the western coastal zone of Tonkin Gulf, the coastal region of the Bac bo, but they are the forth priority for the coastal sub-region of Northeast Bac bo, and the coastal area of Haiphong. Last but not least is the issue of mitigation of beneficiary conflict. However, at each spatial management level and for each stage of management process, one can always find out different priority management issues. In order to succeessfully implement the identified priority issues, there is a need of developing and conducting some core management programs. These programs will go throughout three management periods, but still have some highlight points in different spatial management levels, and each stage of the management process